Analysis of legal stratagems cases in the Quran and Sunnah - Muhammad Omer Rafique; Ahmad Sufyan Che Abdullah; Mohd Abd Wahab Fatoni (Pusat Kelestarian Turath Islami, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2021)
Legal stratagems or Hiyal are the means to reach an end in an unconventional way. Every law consists of this kind of exits for special cases, but these concessions can become a source to circumvent the objectives of the law. Islamic law is the divine law regulated by Allah SWT for all human beings. The primary foundations of this law are the Holy book of Allah SWT and the life of His Prophet PBUH. The researcher aims to analyze the twelve stratagem cases mentioned in the Quran and Sunnah to extract a generalized ruling about applying Ḥilah in Islamic law. The researcher studied each and every case, its background, impact, related department of Islamic law in detail. He found that Ḥiyal are permissible subject to the intensity of need, the intention of the doer, and not evading the higher object of Shari’ah. Some cases of Quran and Sunnah are not pure legal stratagems, but dual meaning sentences used for a valid purpose.